2017
DOI: 10.1007/s10900-017-0375-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Parental BMI and the Family Nutrition and Physical Activity Environment in a Community Sample

Abstract: The purpose of this study was to examine the relationship between parental BMI and the family environment and determine if differences exist in child diet and physical activity related parenting behaviors by parental BMI in a community sample of families recruited through elementary schools in a local school district. We found an association between parental BMI category and family nutrition and physical activity (FNPA) score. Families with an underweight or normal weight parent had a larger proportion (64.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…Similarly Haycraft and colleagues [73] found significantly higher reports of mothers with overweight/obesity giving their child more control around eating, as assessed by the CFPQ, in comparison to mothers with healthy-weight. In contrast, two cross-sectional studies reported no significant differences between parents with healthy-weight, overweight and obesity and CFQ control [75] and PSEAS control [87].…”
Section: Parental Controlmentioning
confidence: 79%
See 3 more Smart Citations
“…Similarly Haycraft and colleagues [73] found significantly higher reports of mothers with overweight/obesity giving their child more control around eating, as assessed by the CFPQ, in comparison to mothers with healthy-weight. In contrast, two cross-sectional studies reported no significant differences between parents with healthy-weight, overweight and obesity and CFQ control [75] and PSEAS control [87].…”
Section: Parental Controlmentioning
confidence: 79%
“…Costa and colleagues [72] suggested that rather than parental weight, parental concern about their child's weight, i.e., where the child is at risk of developing overweight or is already overweight, is related to parental monitoring of their child's eating which questions the direction of this relationship. In contrast, another study using the PSEAS, reported that underweight and healthy-weight parents monitor their child's diet significantly more than parents with overweight and obesity [87], suggesting that parents with overweight and obesity monitor their child's diet less.…”
Section: Monitoringmentioning
confidence: 85%
See 2 more Smart Citations
“…On the other hand, there was a significant correlation between fathers' and mothers' BMI (Spearman, r = 0.15, p = 0.043). This finding suggested that either dietary characteristics of the parents were important in childhood obesity, or that they all shared a similar obesogenic environment [27]. However, an additional limitation of this study was a lack of detailed information about family eating attitudes, cooking patterns, and food content.…”
Section: Discussionmentioning
confidence: 90%